Evolutionary adaptation under climate change: Aedes sp. demonstrates potential to adapt to warming - Lisa I. Couper; Tristram O. Dodge; James A. Hemker; Bernard Y. Kim; Moi Exposito-Alonso; Rachel B. Brem; Erin A. Mordecai; Mark C. Bitter (Proceedings of the National Academy of Sciences, 2025)
Climate warming is expected to shift the distributions of mosquitoes and mosquito-borne diseases, promoting expansions at cool range edges and contractions at warm range edges. However, whether mosquito populations could maintain their warm edges through evolutionary adaptation remains unknown. Here, we investigate the potential for thermal adaptation in Aedes sierrensis , a congener of the major disease vector species that experiences large thermal gradients in its native range, by assaying tolerance to prolonged and acute heat exposure, and its genetic basis in a diverse, field-derived population. We found pervasive evidence of heritable genetic variation in mosquito heat tolerance, and phenotypic trade-offs in tolerance to prolonged versus acute heat exposure. Further, we found genomic variation associated with prolonged heat tolerance was clustered in several regions of the genome, suggesting the presence of larger structural variants such as chromosomal inversions. A simple evolutionary model based on our data estimates that the maximum rate of evolutionary adaptation in mosquito heat tolerance will exceed the projected rate of climate warming, implying the potential for mosquitoes to track warming via genetic adaptation.